2022
DOI: 10.1097/cad.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic response to crizotinib in a breast cancer patient with ALK gene rearrangement

Abstract: Rearrangements of the anaplastic lymphoma kinase (ALK) gene are present in 3–5% of non–small-cell lung cancer (NSCLC), while it was 0.2% in NSCLC tumors. Due to its low frequency, it is extremely challenging to conduct randomized clinical trials of ALK-targeted therapies in NSCLC tumors. In the present case, we describe the first reported case of triple-negative breast cancer (TNBC) harboring the ALK fusion mutation that responded to ALK-targeted therapy after progression with two lines of chemotherapy. Search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Role of HGF derived from SNs in the 4T1 BC colonization in tibiae, and lung metastasis from tibiae, and induction of BCIBP in the 4T1 BC mice To validate the role of HGF in 4T1 BC progression in bone and metastasis to lung in the 4T1 BC mice, we determined the effects of crizotinib, a small compound of c-Met/ALK tyrosine kinase inhibitor, which has been shown to have bene cial effects in patients with non-small cell lung cancer 43 and breast cancer 44 . Our results demonstrated that oral administration of crizotinib signi cantly inhibited the development of osteolytic lesions associated with 4T1 BC colonization in tibiae (Fig.…”
Section: Expression Of Hgf In Sns In Drg and Bonementioning
confidence: 99%
“…Role of HGF derived from SNs in the 4T1 BC colonization in tibiae, and lung metastasis from tibiae, and induction of BCIBP in the 4T1 BC mice To validate the role of HGF in 4T1 BC progression in bone and metastasis to lung in the 4T1 BC mice, we determined the effects of crizotinib, a small compound of c-Met/ALK tyrosine kinase inhibitor, which has been shown to have bene cial effects in patients with non-small cell lung cancer 43 and breast cancer 44 . Our results demonstrated that oral administration of crizotinib signi cantly inhibited the development of osteolytic lesions associated with 4T1 BC colonization in tibiae (Fig.…”
Section: Expression Of Hgf In Sns In Drg and Bonementioning
confidence: 99%
“…Crizotinib is a drug designed to treat NSCLC with ALK mutation and has shown improvement in previous studies [10]. Crizotinib is approved as a therapy option for ROS-1 rearrangement in many countries, especially in advanced non-small-cell lung carcinoma [11,12].…”
Section: Introductionmentioning
confidence: 99%